Analisis Perbandingan Indeks Keandalan Sistem Jaringan Distribusi dengan Metode Section Technique dan Reliability Index Assessment (RIA): Studi Kasus Gardu Induk Balaraja - Ulfah Khairiyah Luthfiyani; Adi Setiawan; Samsul Arifin (Yayasan Literasi Sains Indonesia, 2023)
The reliability of the electric power distribution system refers to its ability to provide sufficient electricity supply to consumers with satisfactory quality. There are several methods used to calculate the level of reliability of a distribution system, such as the Section Technique method and the Reliability Index Assessment (RIA) method, by considering reliability index values such as the System Average Interruption Frequency Index (SAIFI), System Average Interruption Duration Index (SAIDI), and Customer Average Interruption Duration Index (CAIDI). This study analyzed the reliability of the 20kV distribution system in the Prajurit feeder at the Balaraja main substation. Based on the analysis using the Section Technique method, the reliability index values for the Prajurit feeder were obtained at 2.1876 for SAIFI, 20.9624 for SAIDI, and 9.5823 for CAIDI. The analysis using the RIA method showed reliability index values of 2.2025 for SAIFI, 21.3445 for SAIDI, and 9.6910 for CAIDI. The reliability of the distribution system was also tested using computer simulation, and the reliability index values were found to be 1.5697 for SAIFI, 18.6939 for SAIDI, and 11.9092 for CAIDI. Therefore, based on the analysis, simulation, and reliability index standards stated in SPLN 68-2: 1986, the electric power distribution network in the Prajurit feeder can be categorized as a reliable network.